Dengue, West Nile, and Zika Viruses: Potential Novel Antiviral Biologics Drugs Currently at Discovery and Preclinical Development Stages - Ivo C. Martins; Rafaela C. Ricardo; Nuno C. Santos (MDPI AG, 2022)
Dengue, West Nile and Zika viruses are vector-borne flaviviruses responsible for numerous disease outbreaks in both Hemispheres. Despite relatively low mortality, infection may lead to potentially severe situations such as (depending on the virus): hypovolemic shock, encephalitis, acute flaccid paralysis, Guillain-Barré syndrome, congenital malformations (e.g., microcephaly) and, in some situations, death. Moreover, outbreaks also have major socioeconomic repercussions, especially in already vulnerable societies. Thus far, only generic symptoms relief is possible, as there are no specific treatments available yet. Dengvaxia was the world's first dengue vaccine. However, it is not fully effective. Prophylactic approaches against West Nile and Zika viruses are even more limited. Therefore, therapeutic strategies are required and will be discussed hereafter. We will first briefly present these viruses' epidemiology, life cycle and structure. Then, we introduce the clinical presentation, diagnosis approaches and available vaccines. Finally, we list and discuss promising compounds at discovery and preclinical development stages already deposited at the GlobalData database and divided into three main types, according to therapeutic molecule: antibody-based, peptide-based molecules and, other compounds. To conclude, we discuss and compare promising developments, useful for future therapies against these three flaviviruses of major concern to human health.